2018
DOI: 10.1016/j.istruc.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Shake Table Testing of Concentrically Braced Steel Structures With Realistic Connection Details Subjected to Earthquakes

Abstract: This paper describes an experimental investigation into the seismic response of concentrically braced steel frames (CBFs). Twelve shake table tests were performed on full-scale single storey frames, each containing a pair of identical brace members. The experimental programme examined the behaviour of brace members with four different square and rectangular hollow cross-sections and a range of gusset plate connection details. The aim of the experimental study was to determine the influence of brace and gusset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
7
0
2
Order By: Relevance
“…On the other hand, by testing realistic joints in CBFs under different levels of seismic excitation, Goggins et al [110] found that brace fracture occurred under high-intensity excitations whereas gusset plates remained unfractured if designed with standard linear clearance (SLC) or elliptical clearance (EC) methods. Complementarily, Kanyilmaz assessed the ductility of bolted joints with gusset plates with angle braces [111].…”
Section: Bolted Connections In Concentrically X Braced Framesmentioning
confidence: 99%
“…On the other hand, by testing realistic joints in CBFs under different levels of seismic excitation, Goggins et al [110] found that brace fracture occurred under high-intensity excitations whereas gusset plates remained unfractured if designed with standard linear clearance (SLC) or elliptical clearance (EC) methods. Complementarily, Kanyilmaz assessed the ductility of bolted joints with gusset plates with angle braces [111].…”
Section: Bolted Connections In Concentrically X Braced Framesmentioning
confidence: 99%
“…Umumnya CBF terdiri dari bagian bresing diagonal yang tersambung ke balok dan kolom dengan menggunakan sambungan pelat gusset [1]. CBF menawarkan ekonomis dan bentuk yang efisien penahan seismik lateral untuk struktur [2]. CBF terbagi menjadi 2 berdasarkan daerah seismik yang mana Ordinary Concentrically Braced Frames (OCBF) dapat digunakan pada daerah rawan gempa rendah sedangkan Special Concentrically Braced Frames (SCBF) yang dapat digunakan pada daerah rawan gempa tinggi [3].…”
Section: Pendahuluanunclassified
“…The experimental and analytical results indicate that the second-order effects are appeared as the acceleration amplitude of the earthquake increased and the results obtained from the shaking table test verified the results of the FE model analysis carried out by the ABAQUS software. Goggins et al (2017), based on the serviceability, ultimate and collapse limit states, investigated experimentally the effect of the gusset plate and brace properties on the concentrically braced frame response. Twelve experiments were examined on full-scale single-story frames.…”
Section: Introductionmentioning
confidence: 99%